Genetic counseling, 2030: An on‐demand service tailored to the needs of a price conscious, genetically literate, and busy world. Issue 2 (9th April 2019) - Rashkin, Misha D.; Bowes, Johnathan; Dunaway, Keith; Dhaliwal, Jasmine; Loomis, Erick; Riffle, Stephen; Washington, Nicole L.; Ziegler, Chris; Lu, James; Levin, Elissa
Abstract: The practice of genetic counseling is going to be impacted by the public's expectation that goods, services, information, and experiences happen on demand, wherever and whenever people want them. Building from trends that are currently taking shape, this article looks just over a decade into the future—to 2030—to provide a description of how the field of genetics and genetic counseling will be changed, as well as advice for genetic counselors for how to prepare. We build from the prediction that a large portion of the general public will have access to their digitized whole genome sequence anytime, any place, on any device. We focus on five topics downstream of this prediction: public health, personal autonomy, polygenic scores (PGS), evolving clinical practices, and genetic privacy.